A systematic review of sex and age factors in neuroleptic malignant syndrome diagnosis frequency. (1st February 2017) - Gurrera, Ronald J.
Abstract : Objective: To examine sex and age distributions in neuroleptic malignant syndrome (NMS) patients based on a systematic literature review. Method: EMBASE and PubMed databases were searched to identify any observation of NMS published from January 1, 1998 through November 1, 2014 that was accessible and interpretable (using language translation software). Redundant and equivocal reports were excluded. Sex ratio and age distributions were examined using standard graphical techniques and measures of association. Results: Twenty‐eight independent sex ratio estimates were included. Males predominated in most (75%) estimates with an overall median sex ratio of 1.47 (95% CI, 1.20–1.80). NMS incidence peaked at age 20–25 years and declined steadily thereafter, with males consistently outnumbering females at all but the oldest age intervals. Conclusion: NMS patients are 50% more likely to be males, and NMS is most likely to occur in young adulthood.